2*log*x=log*2+log(3*x-4)

Simple and best practice solution for 2*log*x=log*2+log(3*x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2*log*x=log*2+log(3*x-4) equation:


Simplifying
2log * x = log * 2 + log(3x + -4)

Multiply glo * x
2glox = log * 2 + log(3x + -4)

Reorder the terms for easier multiplication:
2glox = 2glo + log(3x + -4)

Reorder the terms:
2glox = 2glo + glo(-4 + 3x)
2glox = 2glo + (-4 * glo + 3x * glo)
2glox = 2glo + (-4glo + 3glox)

Combine like terms: 2glo + -4glo = -2glo
2glox = -2glo + 3glox

Solving
2glox = -2glo + 3glox

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '2glo' to each side of the equation.
2glo + 2glox = -2glo + 2glo + 3glox

Combine like terms: -2glo + 2glo = 0
2glo + 2glox = 0 + 3glox
2glo + 2glox = 3glox

Add '-3glox' to each side of the equation.
2glo + 2glox + -3glox = 3glox + -3glox

Combine like terms: 2glox + -3glox = -1glox
2glo + -1glox = 3glox + -3glox

Combine like terms: 3glox + -3glox = 0
2glo + -1glox = 0

Factor out the Greatest Common Factor (GCF), 'glo'.
glo(2 + -1x) = 0

Subproblem 1

Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing g to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Add 'x' to each side of the equation. -1x + x = -2 + x Combine like terms: -1x + x = 0 0 = -2 + x Simplifying 0 = -2 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 10+x-7x=-38 | | 8x+6(1+5x)=2 | | 6.1+1= | | 7+7k=147 | | 2/3m-1/3=5/12 | | 8-3y=2(3+y)-5 | | -2(n-4)=10-2N | | -2y-5+2y^2=0 | | 8x+6(1+5x)= | | 4-2(2w-3)=6w-90 | | -6-4=-7a-5 | | 5/2x=(x-5) | | y=3sinx+2cosx | | a+a+5.80+0.5(5.80+a)+3(0.5(5.80+a))=246.20 | | 5+3(n+1)=2n | | 5z^2(z^2+2)=24-16z^2 | | -6x+10=15-6x | | 3x(2+3y)= | | 5-4(10+8m)=39+5m | | (5x)/(3iy)=5-6i | | x(x+3)-6(x+3)=0 | | (y-x)(y+11x)=a^2-b^2 | | c+8+2c=-10 | | -60=-6+6a | | (y-x)(y+11x)=y^2-x^2 | | -0.151-0.008n=4.1 | | 3y-9+3-4y=y+y-18 | | -0.151=-0.008x+4.15 | | 8.3x-3.1(x-4)=-29.04 | | X=0.75+0.35 | | (x-5)(4x-9)=0 | | 5+1.5(d-1)=0.5 |

Equations solver categories